PENGARUH ISLAM DALAM KESENIAN DAN KEBUDAYAAN DI PULAU JAWA - andes rehulina andes (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2024)
This study investigates the influence of Islam on the arts and culture of Java, one of the regions with the richest cultural heritage in Indonesia. Islam spread to Java in the 13th century through trade routes and the preaching of the Songo saints. Santo Songo played an important role in integrating Islamic teachings into the life of Javanese society. The influence of Islam on Javanese art and culture can be seen in various forms, including fine arts, music, dance, theater and traditional rituals. In the field of art, Islamic influence can be seen in batik motifs that combine Islamic symbols with local aesthetics, as well as in carvings that decorate buildings and cultural assets. Gamelan music and shadow puppet art also show adaptation to Islamic values, and the stories are based on Islamic teachings and ethics. Traditional dances, such as Sufi dance, reflect spiritual practices embedded in Javanese traditions. In the cultural field, Islam has influenced traditional rituals and religious ceremonies, and many Hindu and Buddhist traditions have been adapted to Islamic values, creating new, harmonious forms. The Javanese philosophy of life, known as the Javanese concept, combines Islamic spirituality and local wisdom, giving birth to a unique syncretism. The study concluded that the influence of Islam not only enriched Javanese art and culture, but also helped shape a dynamic and tolerant cultural identity that continues to develop and adapt today.